"Eat, my child". Overweight and obesity among children in developing countries - Dimitrios Minos (Georg-August-Universität Göttingen, Courant Research Centre - Poverty, Equity and Growth (CRC-PEG), 2016)
Childhood obesity in developing countries is a topic that hasn't found its way in the economic literature yet. Despite the fact that obesity rates are rising worldwide and the phenomenon is very present even among the poorest of households in developing countries, most of the attention is still drawn towards industrialized ones. This paper utilizes the South African NIDS panel data set to highlight some of the aspects policy makers should bear in mind. In particular, drivers of the phenomenon and their resulting policy options that are widely used in industrialized countries may not be appropriate in a developing setting, especially in one where excess body weight is considered by many as a positive outcome.
Keywords: I12; I18; P46; 330; obesity; nutrition transition; developing country; South Africa